The Effect Of Financial Ratios And Economic Value Added on Company's Market Value - Rumiasih, N.A; Asvariwangi, Verni; Yudiana; Rantika, Mira (Universitas Ibn Khaldun Bogor, 2023)
This study aims to examine and analyze the effect of financial ratios and Economic Value Added on Market Value Added in Islamic Commercial Bank BUMN in Indonesia. The data used are secondary data in the form of financial statements of BRI Syariah, BNI Syariah, and Bank Syariah Mandiri in 2017-2019. The samples used were three companies with a purposive sampling method. The research data analysis stage is multiple linear analysis. The results of the study simultaneously showed that CAR, BOPO, FDR, NPF, and EVA affect the Market Value Added. Partially CAR and FDR has no effect on stock prices. NPF affecting the Market Value Added. This means that every increase in NPF will raise Market Value Added, while BOPO and EVA has a negative influence on Market Value Added, meaning that any increase in BOPO and EVA will reduce Market Value Added.